SLEEP AND ACADEMIC PERFORMANCE - Iqbal, Muhammad Javed; Akbar, Muhammad Siddiq; Khalid, Rana Muhammad; Iqbal, Tehseen (Pakistan Journal of Physiology, 2018)
Background: Sleep is an essential physiological process for life. Its quality is strongly related to psychological and physical health and other measures of well-being. Good quality sleep and adequate amount of sleep are important in order to have better cognitive performance and avoid health problems and psychiatric disorders. Sleep disturbances are an important issue among medical students and residents. This study was designed to find out the relationship between the academic performance of students with their sleep habits. Methods: A total number of one hundred apparently normal healthy students of First year MBBS Class were divided into three groups on the basis of their sleep habits before and after admission in to the medical college as follows: Group-1: Who had the same quality and duration of sleep in medical college as before admission. Group-2: Who had more sleep duration after admission to medical college. Group3: Who had less sleep duration after admission to medical college. The academic performance of these three groups was compared by taking into consideration the percentage of marks obtained in the annual examination of first year MBBS class. Results: Fifty percent of Group-1, and 50% of Group-2 students secured more than 70% marks in the First Year MBBS while 37% of Group-3 students obtained more than 70% marks in First Year MBBS. Conclusion: Disturbance in sleep affects academic performance adversely. Decreased sleep duration affects the academic performance more adversely as compared with the increased sleep duration. Pak J Physiol 2018;14(2):41–2